Autologous connective tissue graft or xenogenic collagen matrix with coronally advanced flaps for coverage of multiple adjacent gingival recession. 36‐month follow‐up of a randomized multicentre trial. (6th May 2021) - Tonetti, Maurizio S.; Cortellini, Pierpaolo; Bonaccini, Daniele; Deng, Ke; Cairo, Francesco; Allegri, Mario; Conforti, Gianpaolo; Graziani, Filippo; Guerrero, Adrian; Halben, Jan; Malet, Jacques; Rasperini, Giulio; et al.
Abstract: Aim: To report the 36‐month follow‐up of a trial comparing the adjunct of a xenogenic collagen matrix (CMX) or connective tissue graft (CTG) to coronally advanced flaps (CAF) for coverage of multiple adjacent recessions. Material and methods: 125 subjects (61 CMX) with 307 recessions in 8 centres from the parent trial were followed‐up for 36 months. Primary outcome was change in position of the gingival margin. Multilevel analysis used centre, subject and tooth as levels and baseline parameters as covariates. Results: No differences were observed between the randomized and the follow‐up population. Average baseline recession was 2.6 ± 1.0 mm. 3‐year root coverage was 1.5 ± 1.5 mm for CMX and 2.0 ± 1.0 mm for CTG (difference of 0.32 mm, 95% CI from −0.02 to 0.65 mm). The upper limit of the confidence interval was over the non‐inferiority margin of 0.25 mm. No treatment differences in position of the gingival margin were observed between 6‐ and 36‐month follow‐up (difference 0.06 mm, 95% CI −0.17 to 0.29 mm). Conclusion: CMX was not non‐inferior with respect to CTG in multiple adjacent recessions. No differences in stability of root coverage were observed between groups and in changes from 6 to 36 months. Previously reported shorter time to recovery, lower morbidity and more natural appearance of tissue texture and contour observed for CMX in this trial are also relevant in clinical decision‐making.